Odpowiedzi

Najlepsza Odpowiedź!
2010-01-08T10:11:03+01:00
A.3x/2+3 2/3=x/3-3 1/2 (*6)
6(3x/2)+6(11/3)=6(x/3)-6(7/2)
9x+22=2x-21
9x-2x=-21-22
7x=-43
x=-6 1/7

B.x/4-1 1/6=3x/4+1 1/5 (*30)
30(x/4)-30(7/6)=30(3x/4)+30(6/5)
15x-35=45x+36
15x-45x=36+35
-30x=71
x=-71/30
x=-2 11/30

C.5x/6-1 2/3==4x/3+1/2 (*6)
6(5x/6)-6(5/3)=6(4x/3)+6(1/2)
5x-10=8x+3
5x-8x=3+10
-3x=13
x=-4 1/3

D.4x/5+3 2/3=4x/3+2 1/5 (*15)
15(4x/5)+15(11/3)=15(4x/3)+15(11/5)
12x+55=20x+33
12x-20x=33-55
-8x=-22
x=2 3/4

E.2x/5-1 2/7=2x/7+2 1/5 (*35)
35(2x/5)-35(9/7)=35(2x/7)+35(11/5)
14x-45=10x+77
14x-10x=77+45
4x=122
x=30 1/2

F.x/8+3 1/3=5x/12+ 2 7/8 (*24)
24(x/8)+24(10/3)=24(5x/12)+24(23/8)
3x+80=10x+69
3x-10x=69-80
-7x=-11
x=1 4/7

G.x/9-3 2/3=2x/3-4 3/8 (*72)
72(x/9)-72(11/3)=72(2x/3)-72(35/8)
8x-264=48x-315
8x-48x=264-315
-40x=-51
x=1 11/40